How Nano‐Ions Act Like Ionic Surfactants. (3rd March 2020) - Hohenschutz, Max; Grillo, Isabelle; Diat, Olivier; Bauduin, Pierre
Abstract: Recently, nanometric ions were shown to adsorb to hydrated neutral surfaces and to bind to the cavities of macrocyclic molecules with an unexpectedly strong affinity arising from a solvent‐mediated effect named superchaotropicity. We show here that nano‐ions at low concentrations (μm range), similarly to anionic surfactants, induce the spontaneous transformation of a swollen lyotropic lamellar phase of non‐ionic surfactant into a vesicle phase. This transition occurs when the neutral lamellae acquire charges, either by adsorption of the nano‐ions onto, or by anchoring of the ionic surfactant into the lamellae. In contrast to ionic surfactants, nano‐ions strongly dehydrate the neutral surfactant assemblies. As a conclusion, these purely inorganic nanometric ions act as alternatives to the widely used organic ionic surfactants. Abstract : Ungeladen, trotzdem willkommen : Anorganische Nano‐Ionen verhalten sich wie (organische) ionische Tenside, wenn sie einer verdünnten Lösung nicht‐ionischer Tenside hinzugefügt werden. Dies verursacht spontane Vesikelbildung durch Adsorption und eine elektrische Aufladung der nicht‐ionischen lamellaren Phase. Obwohl sie fundamental unterschiedlich sind, können Nano‐Ionen als Alternativen zu ionischen Tensiden eingesetzt werden.